“#Repealthe8th”: Ireland, Abortion Access and the Movement to Remove the Eighth Amendment - Sinéad Kennedy (Antropologia, 2018)
Abortion is illegal in almost all circumstances in Ireland, permitted only where there is a risk to the life of the woman due to the eighth amendment to the Irish Constitution. While abortion is banned, women living in Ireland do access abortion; they do so legally by travelling abroad, and illegally within Ireland by accessing the abortion pill online. This access is highly mediated by race, class and migration status. This article will consider the politics of Ireland’s abortion ban through the prism of public debates around abortion, reflecting on the discursive devices employed to both challenge and uphold the status quo on abortion. This conclusion will focus on different dimensions of the “Repeal” movement; a movement that propelled Ireland to finally face up to the reality of abortion and change it laws through removing the eighth amendment from the constitution.